Activated Carbon Derived From Pentace Triptera, Intsia Bijuga And Hevea Brasiliensis Sawdust Via Microwave-Induced Potassium Hydroxide Activation For Dyes Adsorption - Khasri, Azduwin (2019)
Synthetic dyes are widely applied in various industries which has resulted in the water pollution. Therefore, this study aims to synthesis activated carbon (AC) from Pentace triptera (PS), Intsia bijuga (IS) and Hevea brasiliensis (HS) for blue (MB) and remazol brilliant violet 5R (RBV) dye adsorption via microwave-induced potassium hydroxide (KOH) activation adopted together with carbon dioxide (CO2) gasification. Optimum preparation conditions for all ACs prepared were determined using response surface methodology (RSM). ISAC showed high Bruneaur-Emmet-Teller (BET) surface area and total pore volume of 952.23 m2/g and 0.584 cm3/g, respectively compared to PSAC and HSAC. All adsorbents best fitted to the Langmuir isotherm model with ISAC showed higher maximum monolayer adsorption capacity (Qm) of 434.78 and 212.77 mg/g, respectively for MB and RBV dye at 30ºC. Kinetic studies showed that all system followed a pseudo-second order model with film diffusion was the rate-limiting step controlling adsorption. Thermodynamic studies confirmed that all systems were endothermic in nature. For the column studies, the better correlation of breakthrough data shown by Thomas and Yoon-Nelson model. The ACs had good reusability performance for MB and RBV adsorption especially up to three cycle using ethanol as solvent.